The Women and Entrepreneurship in Armenia - Hovhannisyan, Tamara (Bulletin of Yerevan University G: Economics, 2014)
Entrepreneurs are creators of wealth, new jobs, new products and services. These Schumpeterian entrepreneurs destroy the existing market equilibrium with their innovations and create a new one. Despite these facts, the Armenian scientific community knows very little about their motivations, their unique talents and psychological characteristics, human capital and family background. In 2013-2014 the author with closed, fixed-response interview examined 153 Armenian founders of commercial organizations. She studied gender differences in age, marital status, formal education, work experience, family background, motives, self-assessment of leadership skills and risk-taking behavior.